Gas accretion and galactic fountain flows in the Auriga cosmological simulations: angular momentum and metal redistribution. Issue 4 (18th October 2019) - Grand, Robert J J; van de Voort, Freeke; Zjupa, Jolanta; Fragkoudi, Francesca; Gómez, Facundo A; Kauffmann, Guinevere; Marinacci, Federico; Pakmor, Rüdiger; Springel, Volker; White, Simon D M
ABSTRACT: Using a set of 15 high-resolution magnetohydrodynamic cosmological simulations of Milky Way formation, we investigate the origin of the baryonic material found in stars at redshift zero. We find that roughly half of this material originates from subhalo/satellite systems and half is smoothly accreted from the intergalactic medium. About 90 per cent of all material has been ejected and re-accreted in galactic winds at least once. The vast majority of smoothly accreted gas enters into a galactic fountain that extends to a median galactocentric distance of ∼20 kpc with a median recycling time-scale of ∼500 Myr. We demonstrate that, in most cases, galactic fountains acquire angular momentum via mixing of low angular momentum, wind-recycled gas with high angular momentum gas in the circumgalactic medium (CGM). Prograde mergers boost this activity by helping to align the disc and CGM rotation axes, whereas retrograde mergers cause the fountain to lose angular momentum. Fountain flows that promote angular momentum growth are conducive to smooth evolution on tracks quasi-parallel to the disc sequence of the stellar mass-specific angular momentum plane, whereas retrograde minor mergers, major mergers, and bar-driven secular evolution move galaxies towards the bulge sequence. Finally, we demonstrate that fountain flows act to flatten and narrow the radial metallicity gradient and metallicity dispersion of disc stars, respectively. Thus, the evolution of galactic fountains depends strongly on the cosmological merger history and is crucial for the chemodynamical evolution of Milky-Way-sized disc galaxies.